Cherokee Americans : the eastern band of Cherokees in the twentieth century - Finger, John R., 1939- (Indians of the Southeast., 1991)
Finger is a descendant of the tribal remnant that avoided removal in the 1830s and instead remained in North Carolina. Most now live on a reservation adjacent to Great Smoky Mountains National Park.